2022
DOI: 10.1523/jneurosci.1717-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Amygdala, Orbitofrontal and Hippocampal Contributions to Reward and Loss Coding Revealed with Human Intracranial EEG

Abstract: Neurophysiological work in primates and rodents have shown the amygdala plays a central role in reward processing through connectivity with the orbitofrontal cortex (OFC) and hippocampus. However, understanding the role of oscillations in each region and their connectivity in different stages of reward processing in humans has been hampered by limitations with non-invasive methods such as poor spatial and temporal resolution. To overcome these limitations, we recorded local field potentials (LFPs) directly fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 73 publications
(118 reference statements)
4
18
0
Order By: Relevance
“…27 Within the context of a positive valence domain, high gamma activity in the amygdala was also found to encode outcome value during reward processing. 28 Other authors analyzed amygdala activity via restingstate or naturalistic paradigms to classify neural activity predictive of affective states. 14,16,29,30 Scangos et al examined 24-hour resting-state recordings in 13 patients who were categorized to low-or high-depression groups based on the Patient Health Questionnaire-9 (PHQ-9).…”
Section: Amygdala and Hippocampusmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Within the context of a positive valence domain, high gamma activity in the amygdala was also found to encode outcome value during reward processing. 28 Other authors analyzed amygdala activity via restingstate or naturalistic paradigms to classify neural activity predictive of affective states. 14,16,29,30 Scangos et al examined 24-hour resting-state recordings in 13 patients who were categorized to low-or high-depression groups based on the Patient Health Questionnaire-9 (PHQ-9).…”
Section: Amygdala and Hippocampusmentioning
confidence: 99%
“…32,33 High gamma activity in the OFC was observed during outcome valuation, reward prospect, and reward receipt in gambling and subjective choice tasks. 28,[34][35][36] Implementing a monetary incentive delay task, Manssuer et al found that increased OFC and amygdala theta synchronization encoded reward anticipation, whereas amygdala and OFC high gamma activity was observed during monetary loss. 28 In another study, alpha oscillations from the amygdala were found to modulate OFC activity during valence encoding of simple food choices.…”
Section: Orbitofrontal Cortexmentioning
confidence: 99%
“…Amygdala electrical stimulation was reported to alter the emotional perception of images ( Bujarski et al., 2021 ), whereas Manssuer et al. identified a network constituted by the amygdala, hippocampus, and the orbitofrontal cortex for reward and loss coding, using a monetary incentive delay task during SEEG recording (used to study the neural correlates of incentive receipt anticipation ( Helfinstein et al., 2013 )) ( Manssuer et al., 2022 ). The orbitofrontal cortex has a role also in decision making ( Saez et al., 2018 ), and emotional processing ( Weisholtz et al., 2022 ).…”
Section: Cortical Bmis Beyond Motor Controlmentioning
confidence: 99%
“…The role of the OFC in individual value-based decision-making is well established with converging evidence from lesion, neuroimaging, and electrophysiological studies (Wallis, 2007). The OFC encodes a wide range of valuation-related variables such as probability, reward magnitude, prior expectations, and regret (Camille et al, 2004; Domenech et al, 2020; Manssuer et al, 2022; Padoa-Schioppa & Assad, 2006; Saez et al, 2018). Notably, the medial OFC (mOFC; vmPFC) computes the subjective value (Chib et al, 2009; Hunt et al, 2012; Kable & Glimcher, 2007; Lopez-Persem et al, 2020; Plassmann et al, 2007; Strait et al, 2014).…”
Section: Introductionmentioning
confidence: 99%